2017
DOI: 10.1371/journal.pone.0185847
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intracerebral hemorrhage in hemodialysis patients after reducing aspirin use: A quality-assurance observational study

Abstract: There is so far no international consensus concerning the prescription of antithrombotic agents in hemodialysis patients. It is not clear yet why they cause more bleeding in some patients and are beneficial in others. We therefore tried to find out what triggers bleeding in this population. This is an observational before-and-after study that included all patients undergoing hemodialysis in our center between 2005 and 2015. We divided the study into two phases: phase one (125 patients) where aspirin was used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…If intracerebral bleeding does occur in a dialysis patient, systemic heparinization can increase the hematoma size (30) and worsen the outcome. The use of aspirin was associated with increased intracerebral bleeding in a study and did not confer significant benefit to cardiovascular outcome (31). Our current study showed no significant difference in the average heparin dose and antiplatelet use between the case and control groups.…”
Section: Discussioncontrasting
confidence: 44%
“…If intracerebral bleeding does occur in a dialysis patient, systemic heparinization can increase the hematoma size (30) and worsen the outcome. The use of aspirin was associated with increased intracerebral bleeding in a study and did not confer significant benefit to cardiovascular outcome (31). Our current study showed no significant difference in the average heparin dose and antiplatelet use between the case and control groups.…”
Section: Discussioncontrasting
confidence: 44%
“…The involvement of antiplatelet drugs in causing cerebral hemorrhaging in dialysis patients is controversial. Some studies have reported that antiplatelet drugs do not affect the patient prognosis (13,14), while others have reported that they increase the risk of a poor prognosis among hemodialysis patients with cerebral hemorrhaging (8)(9)(10)(11)(12)(13)(14)(15). Antiplatelet drugs are thought to increase the volume of hematomas, as they are hemorrhagic in nature, and a growing hematoma can irreversibly damage the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding risk (ICH) was more pronounced with aspirin use among patients with severe hypertension (pre-dialysis systolic blood pressure >160 mm Hg). 46 Due to conflicting data regarding risks and benefits of antiplatelet medication use among ESRD patients with AF, there is no consensus or guideline regarding their routine use. Results from a randomized controlled trial to assess aspirin use in ESRD patients to reduce the risk of thrombotic events are awaiting.…”
Section: Use Of Antiplatelet Agents In Esrd For Cva/tia Preventionmentioning
confidence: 99%
“…Risk of bleeding was slightly more pronounced with combination of warfarin and aspirin (HR, 1.71; 95% CI, 0.98 to 2.99; P =0.06). Bleeding risk (ICH) was more pronounced with aspirin use among patients with severe hypertension (pre-dialysis systolic blood pressure >160 mm Hg) [ 46 ]. Due to conflicting data regarding risks and benefits of antiplatelet medication use among ESRD patients with AF, there is no consensus or guideline regarding their routine use.…”
Section: Use Of Antiplatelet Agents In Esrd For Cva/tia Preventionmentioning
confidence: 99%